Application of Organizational Culture Diagnostic Practice as a Means of Improving the Efficiency of the Enterprise - qizi, Omanova Nargiza Rustam (International Journal on Integrated Education, 2023)
Organizational culture of the companies is not the only means of improving employee motivation, but also an effective tool to develop company’s strategic and operational objectives. In this article, organizational culture of “Uzkimyosanoat” joint stock company is analyzed by using model of Denison and Complex method of organizational culture. Based on the results of these models, exact datas and recommendations are provided.